Alkaloids of genus Erythrina: An updated review. Issue 13 (2nd July 2020) - Fahmy, Nouran M.; Al-Sayed, Eman; El-Shazly, Mohamed; Nasser Singab, Abdel
Abstract: Genus Erythrina (Fabaceae) comprises several species, which are widely distributed in tropical and subtropical regions of the world. The plants of this genus exhibited significant role in traditional medicine targeting different diseases. Alkaloids and flavonoids were reported as the chief bioactive constituents of this genus with a wide range of biological activities. About 143 alkaloids were isolated from Erythrina sp. Anticonvulsant, anxiolytic, curare-like activity, insecticidal and cytotoxic activities were reported for Erythrina sp. alkaloids. The present work is an overview of the isolated alkaloids from Erythrina sp. with their reported biological activities. Abbreviations: CHCl3: Chloroform; CNS: Central nervous system; DCM: Methylene chloride; DPPH: 2, 2-Diphenyl-1-picrylhydrazyl; E.: Erythrina ; ERα/β: Estrogen receptors α/β; EtOAc: Ethyl acetate; EtOH: Ethanol; Hep-G2: Human liver carcinoma cell lines; HIV: Human immunodeficiency virus; HL-60: Human promyelocytic leukemia cells; K-562: Human immortalized myelogenous leukemia cell line; LPS: Lipopolysaccharide; MeOH: Methanol; MOLT-4: Acute lymphoblastic leukemia cell line; nAChRs: nicotinic acetylcholine receptors; NO: Nitric oxide; NREM: non-rapid eye movement; Pet. ether: Petroleum ether; RBA: Receptor binder affinity; TRAIL: Tumor necrosis factor (TNF)-related apoptosis-inducing ligand